Теріоморфні зображання в орнаментиці Трипілля (трипільський «звіриний стиль») - Бібіков, С.М. (Археологія, 1989)
Дана стаття — текст доповіді С. М. Бібікова на засіданні Вченої ради ІА АН УPCP у березні 1964 р. На матеріалі нечисленних тоді зооморфних зображень трипільської культури зроблено попередні висновки про їх стильові особливості, семантику і локальні відмінності. В статье рассмотрены зооморфные изображения (в основном фигуры собак) на расписной керамике культуры Триполье-Кукутени, уже служившие объектом внимания многих исследователей (Г. Чайлд, Б. Л. Богаевский и др.). Выделяются реалистические, условно-реалистические с чертами схематизма и сильно схематизированные изображения. Установлено, что процесс схематизации нарастал по мере продвижения трипольцев с запада на восток. Указывается на местное происхождение изображений из еще не выясненного центра. Широкое распространение зооморфных изображений связано ие только с культовыми и эстетическими потребностями, но и со своеобразной «модой».
Все изображения отнесены автором к единому хронологическому горизонту — переходу от этапа В к этапу С, т. е. к началу III тыс. до н. э. The paper deals with zoomorphic images (mainly, figures of dogs) on painted ceramics of the Tripolie-Kukuteni culture. They have already attracted attention of numerous researchers (G. Child, B. L. Bogaevsky, and others). Realistic, conditional-realistic images with features of sketchiness and strongly schematized ones are distinguished. It is stated that the process of schematization grew with migration of Tripolian dwellers from the west to the east to Tripolie. The above images are indicated to be of local origin from the centre not revealed yet. Wide spreading of zoomorphic images is a result not only of cult and aesthetic need but also of original “fashion”.
The author refers all the images to the common chronological horizon—transition from stage В to stage C, that is to the early 3d millenium В. C.